Nucleostemin expression in squamous cell carcinoma of the head and neck - Cada, Zdenek; Boucek, Jan; Dvoranková, Barbora; Chovanec, Martin; Plzák, Jan; Kodets, Roman; Betka, Jan; Pinot, Gian L; Gabius, Hans-Joachim; Smetana, Karel (Anticancer research, 2007)
BACKGROUND: This study presents initial data on presence of nucleostemin--a nucleolar protein typical of stem cells in the normal squamous epithelium of the oropharynx and larynx - in squamous cell carcinoma originating from these epithelia. MATERIALS AND METHODS: Differentiation and proliferation markers such as keratins, beta-catenin, galectin-1, and Ki-67 were studied in parallel with nucleostemin for defining cell characteristics. RESULTS: Nucleostemin was detected in nucleoli of both proliferating basal cells and terminally differentiated suprabasal cells of normal epithelium and in tumor cells. Importantly, malignant transformation was connected with a significant enlargement of nucleostemin-positive nucleoli in these cell types. CONCLUSION: Detection of nucleostemin in head and neck cancer cells, together with the size of nucleoli, may be important in the evaluation of tumor differentiation and biology.
Keywords: orofarynx; proteiny vázající GTP; Cell Nucleolus; nádory hlavy a krku; jaderné proteiny; imunohistochemie; Head and Neck Neoplasms; nádorové biomarkery; GTP-Binding Proteins; Carrier Proteins; Oropharynx; lidé; Larynx; Immunohistochemistry; Humans; transportní proteiny; spinocelulární karcinom; Nuclear Proteins; Biomarkers, Tumor; larynx; buněčné jadérko; Carcinoma, Squamous Cell